2007
DOI: 10.1002/ana.21195
|View full text |Cite
|
Sign up to set email alerts
|

Viral load determines the B‐cell response in the cerebrospinal fluid during human immunodeficiency virus infection

Abstract: Our findings demonstrate that HIV infection of the CNS triggers an early profound B-cell response, with plasmablasts serving as the main virus-related B-cell subset in the CSF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 38 publications
(24 reference statements)
4
22
0
Order By: Relevance
“…We focused our analysis on CSF CD138+ cells because prior studies have demonstrated that this predominantly plasma blast population is the primary source of intrathecal Ig production in inflammatory and infectious CNS disease 11, 15, 16, 21. Consistent with the proposed role of AQP4 autoantibodies in NMO pathogenesis, our findings indicate that an intrathecal humoral immune response against AQP4 is evident at the onset of clinical disease.…”
Section: Discussionmentioning
confidence: 62%
“…We focused our analysis on CSF CD138+ cells because prior studies have demonstrated that this predominantly plasma blast population is the primary source of intrathecal Ig production in inflammatory and infectious CNS disease 11, 15, 16, 21. Consistent with the proposed role of AQP4 autoantibodies in NMO pathogenesis, our findings indicate that an intrathecal humoral immune response against AQP4 is evident at the onset of clinical disease.…”
Section: Discussionmentioning
confidence: 62%
“…Most of these cells die by apoptosis, while some traffic to bone marrow or inflamed tissue and become long-lived plasma cells that maintain continuous production of antibodies (reviewed in references 32 and 87). Plasmablasts are also increased during episodes of active systemic lupus erythematosus (59), infectious mononucleosis (49), and acute rotavirus infection (34) and appear at a higher frequency in the cerebrospinal fluid of HIV-infected patients compared to controls (21). We show here that in the setting of chronic HIV infection, plasmablast frequency in the blood is significantly higher in patients than in uninfected donors (1.6% versus 0.46%, P ϭ 0.001).…”
Section: Vol 83 2009 Frequency and Phenotype Of Hiv-specific B Cellmentioning
confidence: 63%
“…We clearly showed the added value of CSF CXCL13 to CSF-RPR, and we also showed that HIV-infected patients benefited more from CSF CXCL13 as an added marker for diagnosis of neurosyphilis. Cepok et al showed that HIV infection triggers an early profound B cell response in CNS, which serves as the main virus-related B cell subset in the CSF (14), and B cells are the main source of CSF CXCL13 (8,13). However, Bremell et al showed that CSF CXCL13 was not increased in HIV-infected patients (15), and we did not observe elevated CSF CXCL13 concentrations in the HIV-and T. pallidum-coinfected control group with a negative CSF-RPR result.…”
Section: Discussionmentioning
confidence: 99%